Absence of evidence dooms former student's suit. Issue 1 (April 2015) - Unknown
Abstract : Case name: Shurb v. The University of Texas Health Science Center at Houston‐School of Medicine, et al., No. 4:13‐CV‐271 (S.D. Texas 10/24/14).